SIMULASI PENGGANTIAN KACA DAN PENGGUNAAN VEGETASI SEBAGAI SUN SHADING TERHADAP SOLAR EXPOSURE GEDUNG PUSAT UNIVERSITAS GADJAH MADA - , MUHAMMAD FITRA ARIEF, Dr.Eng. Mohammad Kholid Ridwan, S.T.,M.Sc ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Central building Universitas Gadjah Mada (UGM) is one of the heritage buildings in the Special Region of Yogyakarta (DIY). Central building of UGM has four sides. The sides can affect the intensity of solar radiation received by each side. Intensity of solar radiation will have an impact on the value of solar exposure, where the value of solar exposure can be used as a reference to determine the level of thermal comfort or lighting comfort inside a room. Calculation of solar exposure also influenced by the constituent materials of the building, especially the translucent material, such as glass. With the variation of the material used, the value of solar exposure will also vary. The addition of vegetation on buildings also affects the value of solar exposure that is accepted by the building, because the vegetation is able to absorb solar radiation. This study intends to measure the solar exposure received by the central building of UGM using simulation in Ecotect. The results of this study is the total value of the absorption of solar radiation in the central building of UGM in one year amounted to 65,700 Wh/m 2 , while the total value of the transmission of sun radiation at 531,593 Wh/m 2 . Another result is the addition of vegetation as a sun shading can increase the level of absorption of solar radiation at 132.28% of the initial conditions.